Pudarnya Ideologi Partai Islam Pascareformasi: Telaah atas Perjalanan Partai Keadilan Sejahtera (PKS) sejak Pemilu 2009-2019 - Wahyudi, Johan (State Islamic Institute of Kudus (IAIN Kudus), 2022)
In the midst of a dilemmatic condition about the consistency of maintaining an exclusive party ideology and the interest of winning the battle in the election, PKS began to carry out an inclusion-moderation strategy since 2009. This research aims to discuss the fading ideology of PKS since the 2009-2019 as one of the Islamic parties that is considered to have the clearest ideology when compared with other Islamic parties and with nationalist parties. This research used qualitative methods, meanwhile the data were collected through literature study. The result is political parties in Indonesia implement various strategies to gain as many votes in elections. There is a tendency to moderate and even marginalize ideologies in favor of winning contestation. Despite having a militant conservative religious voter base, PKS chose to moderates the party's ideology through an inclusion-moderation strategy from the 2009 election to the 2019 election. The fading ideology is a consequence of inclusion-moderation strategy. Therefore, in the context of formulating a public policy agenda, the ideological positions of political parties in Indonesia are almost indistinguishable.